Global Development Finance Projects Slow Growth for 1999 - Aiyar, Swaminathan S.; Brahmbhatt, Milan (World Bank, Washington, DC, 2012)
The growth prospects of developing countries have worsened over the past six months, world trade growth has slowed, capital flows are unlikely to recover to pre-crisis levels in the near term, and, commodity prices are weak. This note reviews the reduced access to international capital flows by most emerging countries, as a result of the financial crises, while dollar export prices for developing countries fell eleven percent in 1998, with both primary commodities, and manufactures suffering. As a result, world trade fell one percent in current dollars in 1998, the first decline since 1993, while global trade volume in goods, grew only four to five percent in 1998, the slowest advance since 1992, barely half the performance in 1997. The note provides an outlook for developing regions, with expected differences in performance between regions, noting significant downside risks to even this somber outlook, and, predicts potential revival of protectionist sentiments in the United States, and Europe, should economic activity contract.